The mentalist. The complete first season [videorecording (DVD)] - Baker, Simon, 1969-; Baker, Simon, 1969-; Tunney, Robin; Kang, Tim, 1973- (Warner Home Video, 2009)
After his wife and child are murdered, fake celebrity psychic Patrick Jane shakes his ruse and uses his powers of observation as an agent for the California Bureau of Investigation.